Analysis of Energy Flow to the Interface Microstructure and Its Effect on Weld Strength in Ultrasonic Additive Manufacturing - Gowtham Venkatraman; Leon M. Headings; Marcelo J. Dapino (Crystals)
Ultrasonic additive manufacturing (UAM) is a process used for the three-dimensional printing of metal foil stock that can produce near-net-shaped metallic parts. This work details the development of an energy-based tool to identify the relationships between input energy, energy stored in the interface microstructure, and the strength of the weld interface in UAM. The stored energy in the grain boundaries of the crystallized grains in the interface microstructure are estimated using the Read–Shockley relationship. The energy stored in the interface is found to be positively correlated with the resulting weld strength. An energy flow diagram is developed to map the flow of energy from the welder to the workpiece and quantify the key participating energies such as the energy of plastic deformation, energy stored in the interface microstructure, energy required for asperity collapse, and heat generation. A better understanding of the flow of energy in UAM can assist in optimizing the process to maximize the portion of energy input by the welder that is used for bond formation.